Clinical analysis of 234 cases with congenital malformations of respiratory system - Zhang, Wei-xi (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2009)
OBJECTIVE: To explore clinical characteristics, radiographic findings and diagnostic methods of patients with congenital malformations of respiratory system for enhancing the diagnosis of congenital malformations of respiratory system in children